Experimental evaluation of the methods for determining the antimicrobial activity of chlorophyllipt - Yu. V. Olefir; A. I. Lutseva; O. V. Gunar; N. G. Sakhno; V. E. Grigorieva (Регуляторные исследования и экспертиза лекарственных средств)
The present article describes the results of a comparative analysis of methods for determining the antimicrobial activity of chlorophyllipt. It mentions the aspects of serial dilution method and shows the advantages of using agar culture medium for subsequent recording of test results performed by the mentioned methods. The possibility of an equivalent use of cup and test-tube methods for the assessment of antimicrobial activity of chlorophyllipt in the form of alcohol and oil extracts has been confirmed. The necessity of exact compliance with the standards of laboratory procedures and initial verification of culture media quality was noted. During the experimental study of the antimicrobial activity of chlorophyllipt, using 4 types of microorganisms, the feasibility of using S. aureus. strain as a test microorganism has been confirmed. The experiment has shown that the choice of the method does not affect the result of the test in terms of «antimicrobial activity» and it only depends on the characteristics of the sample.